Preliminary Study of Assessing Bladder Urinary Volume Using Electrical Impedance Tomography - Li, Rihui; Gao, Jinwu; Li, Yaning; Wu, Junpeng; Zhao, Zhanqi; Liu, Yang (Journal of medical and biological engineering, 2016)
A non-invasive method based on electrical impedance tomography (EIT) is presented for the continuous assessment of human bladder urinary volume. An EIT system developed for bladder urinary volume imaging is first introduced. To validate the system and to examine the feasibility of estimating bladder fullness with EIT, an ex vivo experiment with four porcine bladders and an observational study of bladder urine filling in six healthy volunteers was conducted. Four porcine bladders were filled with saline solution with various concentrations and separately placed in a cylindrical tank. Each bladder was filled from 0 to 600 ml in increments of 100 ml. EIT measurements were performed and the maximum diameters of the bladders were recorded. For the observational study, bladder filling from empty to the status of strong micturition desire was monitored by EIT. The average conductivity index (ACI) was derived from the EIT images to quantify the bladder filling. For comparison, a four-electrode method, which is described in previous studies, was also applied. The results show a high positive linear correlation between the ACI and the bladder urinary volume in all subjects (correlation coefficient R = 0.98 ± 0.01, p < 0.001), with the performance of the four-electrode method being much poorer (correlation coefficient R = −0.27 ± 0.82, p < 0.001). This study demonstrates that EIT has the ability to distinguish bladder urinary volumes and thus has potential as a practical and effective technique for assessing bladder urinary volume.